Leukemia cutis and other dermatological findings in pediatric patients with acute myeloid leukemia - Juan A. Godínez-Chaparro; Adriana Valencia-Herrera; Mario R. Duarte-Abdala; Carlos A. Mena-Cedillos; Mirna E. Toledo-Bahena (Permanyer, 2021)
Background: Leukemia cutis (LC) is the infiltration of neoplastic leukocytes into the skin, causing skin lesions. In children, it appears more frequently in patients with acute myeloblastic leukemia (AML), particularly in subtypes with a monocytic component. Methods: We studied a retrospective cohort including all AML cases from the Hospital Infantil de México Federico Gómez between January 2009 to December 2019 and described the clinical characteristics of those who presented LC and other mucocutaneous manifestations. The information was collected from clinical records and analyzed using SPSS software (version 17). Results: We identified 54 AML cases: 53.7% were males, and 75.9% of the patients presented at least one dermatosis in the course of the disease. LC was clinically present in 14.8% of patients and was histologically confirmed in 9.2% of them; two congenital leukemia cases were identified. Among these patients, LC was more frequent in males. LC patients were younger than those without LC, the most frequent AML subtype was M2 (37.5%), and the most frequent clinical manifestations were plaques, chloromas, and gingival hyperplasia. None of the patients presented LC before AML diagnosis. Conclusions: Currently, only a few studies about LC on pediatric populations have been reported, and the existing ones have small sample sizes. We found clinical and epidemiological similarities with other populations in the studied sample.